Comparison of inpatient admission rates of patients treated with apixaban vs. warfarin for venous thromboembolism in the emergency department. Issue 1 (1st January 2020) - Deitelzweig, Steven; Hlavacek, Patrick; Mardekian, Jack; Rosenblatt, Lisa; Russ, Cristina; Tuell, Kenneth; Lingohr-Smith, Melissa; Lin, Jay; Guo, Jennifer D
ABSTRACT: Objectives : This study evaluated inpatient admission status, hospitalization length of stay (LOS), hospital costs, and readmissions of patients who were diagnosed with venous thromboembolism (VTE) and treated with apixaban or warfarin in the emergency department (ED). Methods : Patients (≥18 years) with an ED visit with a primary discharge diagnosis code of VTE were identified from the Premier Hospital database (8/1/2014-5/31/2018). Patients who received apixaban or warfarin during the ED visit were selected and grouped into two treatment cohorts. Outcomes of ED disposition (discharged or admitted to the inpatient setting), hospital LOS, hospital cost of index event, and rate of 1-month readmissions were compared for the study cohorts. Results : Of the overall study population, 30.5% (n = 12, 174; mean age: 59.7 years) received apixaban and 69.5% (n = 27, 767; mean age: 59.3 years) received warfarin for VTE in the ED. After adjusting for patient and hospital characteristics, the regression analysis showed that apixaban was associated with a significantly lower likelihood of admission to the inpatient setting vs. warfarin (Odds Ratio [OR]: 0.12, 95% Confidence Interval [CI]: 0.12 to 0.13; p < 0.001). Correspondingly, mean index hospital LOS was 1.42 days shorter (95% CI: −1.47 to −1.36; p < 0.001) and mean index event hospital cost per patient was significantly lower by $4, 276 ($3, 732 [95% CI: $3, 565 to $3, 907] vs. $8, 008 [95% CI: $7, 676 to $8, 355]; p < 0.001). Also, the likelihood of all-cause 1-month readmission was significantly lower for patients treated with apixaban vs. warfarin (OR: 0.85, 95% CI: 0.79 to 0.92; p < 0.001). Conclusions : In the real-world setting, VTE patients with an ED visit who were treated with apixaban vs. warfarin had a lower likelihood of being admitted to the inpatient setting, which was reflected in shorter average LOS and lower average index event cost. Additionally, the risk of 1-month readmission was also lower for patients treated with apixaban vs. warfarin.